TAYLOR RULE AND DISCRETIONARY REGIMES IN THE UNITED STATES: EVIDENCE FROM A k-STATE MARKOV REGIME-SWITCHING MODEL. (1st August 2016) - Alba, Joseph D.; Wang, Peiming
Abstract : We examine U.S. monetary policies from 1973 to 2014 with the Taylor rule as a benchmark by utilizing a k -state Markov regime-switching model in which the number and the periods of the regimes are endogenously determined. The model relates the federal funds rate to real time output gaps and inflation forecast. It endogenously identifies the periods of Taylor rule regime and discretionary regimes, consistent with the U.S. experience. The Taylor rule regime also coincides with periods of lower variability in inflation and in real GDP growth.